Electrical properties of 4H-SiC MIS capacitors with AlN gate dielectric grown by MOCVD. (March 2019) - Khosa, R.Y.; Chen, J.T.; Pálsson, K.; Karhu, R.; Hassan, J.; Rorsman, N.; Sveinbjörnsson, E.Ö.
Abstract: We report on the electrical properties of the AlN/4H-SiC interface using capacitance- and conductance-voltage (CV and GV) analysis of AlN/SiC MIS capacitors. The crystalline AlN layers are made by hot wall MOCVD. CV analysis at room temperature reveals an order of magnitude lower density of interface traps at the AlN/SiC interface than at nitrided SiO2 /SiC interfaces. Electron trapping in bulk traps within the AlN is significant when the MIS capacitors are biased into accumulation resulting in a large flatband voltage shift towards higher gate voltage. This process is reversible and the electrons are fully released from the AlN layer if depletion bias is applied at elevated temperatures. Current-voltage (IV) analysis reveals that the breakdown electric field intensity across the AlN dielectric is 3–4 MV/cm and is limited by trap assisted leakage. By depositing an additional SiO2 layer on top of the AlN layer, it is possible to increase the breakdown voltage of the MIS capacitors significantly without having much impact on the quality of the AlN/SiC interface.